(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
The transition to renewable energy systems has emphasized the need for efficient and decentralized energy management strategies. This paper presents an energy trading framework for standalone DC microgrids, integrating community energy storage (CES) and different types of single-sided auction mechanisms. In this framework, households equipped with solar photovoltaic (PV) systems and energy storage units interact with CES as the central trading entity, eliminating direct peer-to-peer transactions. The study aims to identify the clearing price and examined the suitability of three single-sided auction types: Uniform Price Auction (UPA), Generalized Second Price Auction (GSPA) and Pay-as-Bid Auction (PABA). A MATLAB/Simulink-based simulation evaluates the performance of the system, using 24 hours energy generation and consumption profiles for 10 house nodes. Results demonstrate that CES effectively balances energy supply and demand, while auction mechanisms enable fair and efficient market operations. Each auction type exhibits distinct pricing and allocation characteristics, offering flexibility in diverse market conditions. This study highlights the potential of energy trading with different auction types to improve energy management, maintain system stability and encourage renewable energy utilization for standalone microgrid systems.